2018
DOI: 10.1080/00032719.2017.1389950
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Metribuzin with a Cobalt Phthalocyanine-Modified Carbon Paste Electrode

Abstract: Metribuzin is a widely used pesticide with a half-life of up to 2 months and high affinity to organic matter that should be carefully monitored. Here is reported the development of a modified carbon paste electrode using cobalt phthalocyanine as a biomimetic catalyst for the determination of metribuzin. The diffusion coefficient of metribuzin at room temperature was (59 � 16) � 10 −6 cm 2 s −1 and the apparent Michaelis-Menten constant (K ap M) was (7.4 � 0.6) � 10 −6 mol L −1. Electroanalytical measurements w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…These structures are macrocycles with metal centers like iron [22][23][24][25][26][27][28], cobalt [29][30][31][32], copper [33][34][35], and nickel [33,34,36] bearing 4 pyrrolic nitrogen atoms. Porphyrins and phthalocyanines have been used as electrodes and have been reported for a wide range of reactions such as the ORR [32,[37][38][39][40], reduction of CO 2 [41][42][43][44][45], and the oxidation of H 2 O 2 and hydrazine [46,47] organic [48][49][50][51][52], biological [53,54] and inorganic compounds [55][56][57][58][59][60][61][62], as well as other forms of bio-mimicking [63,64]. They are also interesting since they may be readily bound to the surface of electrode materials such as carbon nanomaterials …”
mentioning
confidence: 99%
“…These structures are macrocycles with metal centers like iron [22][23][24][25][26][27][28], cobalt [29][30][31][32], copper [33][34][35], and nickel [33,34,36] bearing 4 pyrrolic nitrogen atoms. Porphyrins and phthalocyanines have been used as electrodes and have been reported for a wide range of reactions such as the ORR [32,[37][38][39][40], reduction of CO 2 [41][42][43][44][45], and the oxidation of H 2 O 2 and hydrazine [46,47] organic [48][49][50][51][52], biological [53,54] and inorganic compounds [55][56][57][58][59][60][61][62], as well as other forms of bio-mimicking [63,64]. They are also interesting since they may be readily bound to the surface of electrode materials such as carbon nanomaterials …”
mentioning
confidence: 99%
“…As illustrated in Figure 3(b) linear dependency between peak current and v can be concluded by the regression equation of Ipa(μA) = 0.6179 + 0.9760 v (R 2 = 0.9993). These results suggest that the electrode process was only by adsorption controlled process over the entire v range [47][48][49][50][51]. Further investigations indicated that logarithm of anodic peak current of analyte was linearly proportional to logarithm of scan rate.…”
Section: Optimization Of CV Parametersmentioning
confidence: 99%